Diverse Patient Experiences of Internet-Based Cognitive Behavioral Therapy with Guided Peer Support for Generalized Anxiety Disorders - Jill Nault Connors PhD, MSSW; Ernani Magalhaes JD; Kevin Prather MSW; Nida Khan MD; Claire Draucker PhD, RN, FAAN; Johanne Eliacin PhD, HSPP; Chet Montgomery; Julie Hayden BS; Michael Millard MD; Kurt Kroenke MD; Paul Musey MD, MS, FACEP (Journal of Patient Experience)
Opportunities exist to improve patient experience in the emergency department for low-risk (ie, non-cardiac) chest pain patients with anxiety and panic as the underlying cause of symptoms. Referral to internet-based cognitive behavioral therapy (iCBT) with guided support is a scalable, evidence-based option that is underused, particularly among non-white patients. In collaboration with a diverse group of patient and community partners, we co-developed and tested an existing iCBT course for generalized anxiety disorder with delivery of guided support by a peer recovery specialist with concordant lived experience. We analyzed patient partner feedback from debriefing sessions during the testing phase using conventional content analysis. Results revealed overall positive experiences with both iCBT lessons and peer support calls. Key points derived from qualitative findings include: (1) iCBT lesson content resonated reasonably well with the diverse group of patient partners, (2) the peer relationship was key to individualizing application of content to various lived experiences, and (3) the guided discussion should be participant-driven and based on content that resonates most with the participant. In conclusion, iCBT with guided peer support was acceptable to patient partners involved in co-development and testing who were representative of a diverse patient population.